Cheyenne Dog Soldier Depredations on Settlers in the Northern Kansas Frontier; From 1864 to 1869 - Howard, Ian (Kansas State University, The Chapman Center for Rural Studies, 2010)
During the 1860s, Indian tribes raided frontier settlements across the plains, most notably the Cheyenne in North Central Kansas. Numerous counties in Kansas felt the scarring effect of the raids; however, the counties of Jewell, Mitchell, Washington, Republic, Cloud, and Clay were the most affected. Almost all sources on the matter report the Indians as "northern Cheyenne." However, the information provided by first-hand accounts points to the Dog Soldiers as being behind the raids. In this study, the author examines the raids that took place in north central Kansas between 1864 – 1869, while demonstrating how and why the Dog Soldiers committed the depredations.
Ian Howard, “Cheyenne Dog Soldier Depredations on Settlers in the Northern Kansas Frontier; From 1864 to 1869,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/214.
Keywords: Cheyenne Dog Soldiers; Chief Little Robe; Dull Knife; Medicine Lodge Treaty; Scandia; Treaty of Fort Wise